2017
DOI: 10.1002/jbm.b.34043
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, characterization, and biocompatibility assessment of a novel elastomeric nanofibrous scaffold: A potential scaffold for soft tissue engineering

Abstract: With regard to flexibility and strength properties requirements of soft biological tissue, elastomeric materials could be more beneficial in soft tissue engineering applications. The present work investigates the use of an elastic polymer, (polycaprolactone fumarate [PCLF]), for fabricating an electrospun scaffold. PCLF with number-average molecular weight of 13,284 g/mol was synthetized, electrospun PCLF:polycaprolactone (PCL) (70:30) nanofibrous scaffolds were fabricated and a novel strategy (in situ photo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, the peak at 1471 cm −1 pertained to CH 2 bending vibration, and the four peaks at 1364, 1240, 1166, and 1049 cm −1 were assigned to C-O stretching vibration. 49,50 The pure PPDO nanofibrous meshes included several characteristic peaks at 2914, 1739, 1432, 1294, 1128, and 1052 cm −1 , which were assigned to C-H stretching vibration, C=O stretching vibration, the CH 2 bending vibration absorption peak, and C=O the stretching vibration absorption peak, respectively. 31 Importantly, all of the above-mentioned characteristic peaks for PCL and PPDO components were observed in the three PCL/PPDO nanofibrous meshes with different PCL/PPDO mass ratios.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the peak at 1471 cm −1 pertained to CH 2 bending vibration, and the four peaks at 1364, 1240, 1166, and 1049 cm −1 were assigned to C-O stretching vibration. 49,50 The pure PPDO nanofibrous meshes included several characteristic peaks at 2914, 1739, 1432, 1294, 1128, and 1052 cm −1 , which were assigned to C-H stretching vibration, C=O stretching vibration, the CH 2 bending vibration absorption peak, and C=O the stretching vibration absorption peak, respectively. 31 Importantly, all of the above-mentioned characteristic peaks for PCL and PPDO components were observed in the three PCL/PPDO nanofibrous meshes with different PCL/PPDO mass ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study has shown that the UV-spinning onto a plate collector submerged in a solvent for the un-cross-linked materials can lead to strikingly different mechanical properties compared to the more conventional “dry” UV ES. 204 This aspect can also further contribute to expanding the range of mechanical properties achievable with the desired polymer network.…”
Section: Reactive Electrospinningmentioning
confidence: 99%
“…Scaffolds with tailored substrates are another way to create three dimensional (3D) structures which guide cell phenotype. These scaffolds can be made of various materials, such as polymers, ceramics or metals and scaffold design should be customized for the biological environment being mimicked and the cell type used (70)(71)(72). As an example, Granziano et al used scaffolds with tailored surface geometry to polarize dental pulp stem cells to enhance differentiation as well as proliferation (73).…”
Section: Microfabrication Techniques To Study Cell Polaritymentioning
confidence: 99%